Civilizational and ethical aspects of environmental safety - Marković, Danilo Ž. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
These considerations of civilizational and ethical aspects of environmental safety start by a reference to the conceptual determination of this safety, and its foundation on a concepton of the Planet Earth as a political and geological space, originating in the development of life forms. In this sense, the author understands the structures of the Earth’s ecosystem, its unity, and the disruption of this unity with consequences for its survival and the survival of the human civilization itself. In the context of this approach, the author points to the need to preserve the environmental safety from the standpoint of equality and justice, stressing that justice is a legal category, especially when it is associated with the laws of nature, laws which are also associated with man as a natural being.